Strategies for Sustainable Development: Leveraging Demographic Factors in Indonesia's Regions - Siregar, Zulkifli; Nasution, Zulkifli; ., Rujiman; Purwoko, Agus (Journal of Ecohumanism, 2024)
This study investigates the impact of demographic factors on the demographic bonus and regional development in Indonesia, using a sample of 30 provinces from 2011 to 2019. Population growth positively influences both the demographic bonus and regional development. In contrast, life expectancy and contraceptive prevalence rate have negative effects on the demographic bonus. The school-age population positively impacts both the demographic bonus and regional development. The demographic bonus negatively affects regional development and fails to mediate the relationship between population growth and regional development. However, it mediates the effects of life expectancy and the school-age population on regional development. The analysis employs descriptive analysis and structural equation modelling (SEM) using Smart-PLS. The findings recommend effective management of population growth, enhanced healthcare to improve life expectancy, and balanced birth control programs. Increased investment in education and inclusive development strategies are vital. Policies should facilitate the active participation of the working-age population, supported by continuous research and development to ensure responsive policy formulation. These recommendations aim to maximize the potential of the demographic bonus and support sustainable regional development in Indonesia.